Application and case studies of magnetic induction - Arshad, Atika; Tasnim, Rumana; Khan, Sheroz; Alam, A. H. M. Zahirul (IIUM Press, 2011)

(untitled)
The on-going development in the field of sensors applications has opened up several possibilities for significant improvements in the advancement of bio-implantable devices or medical equipment. Some researchers have designed and developed inductive sensors for various applications such as tongues drive system enabling a person with severe disabilities to sense. It determines users' intentions by tracking the movements of a permanent magnetic tracer wirelessly that is secured on their tongues using an array of magnetic sensors